Анализ динамических нагрузок главного электропривода клети стана горячей прокатки - Задорожний, Николай Алексеевич; Переходченко, Виктор Александрович; Задорожняя, Инна Николаевна; Литвинов, О. А. (НТУ "ХПИ", 2010)
For research of dynamic processes in the electromechanical system of drive of the rolling mils generalized indexes of electromechanical intercommunication are used. During optimization of dynamic processes correlations of parameters of maximum effect of damping of resilient mechanical vibrations are set. It is suggested to promote a resource of mechanical equipment due to the decline of vibrating the dynamic loading.
Analysis of the dynamic loadings of main electrical drive of cage of the hot rolling mill
Keywords: демпфирование; жесткость; система электромеханическая; двигатель синхронный